Faktor-Faktor Yang Mempengaruhi Independence Assurance Laporan Keberlanjutan - Riwayadi Riwayadi (Jurnal Akuntansi dan Governance Andalas, 2019)
The aim of this research is to determine the factors influencing the independent assurance of sustainability report. The type of this research is quantitative research using secondary data which are determined by purposive sampling. The population is the sustainability reports prepared based on GRI Standard which are published by non-banking and financial companies for period of 2011 - 2016. Independent assurance is used as dependent variable, and industry, profitability, liquidity, and solvability are used as independent variables. T-test is used for partial test and F-test for simultaneous test. This research finds that profitability and solvability partially have significant influence on independent assurance while industry and liquidity partially have no significant influence on independent assurance. However, industry, profitability, liquidity, and solvability simultaneously have significant influence on independent assurance of sustainability report. Independent assurance is influenced for 27,2% by industry, profitability, liquidity, and solvability while the remaining of 72,8% is influenced by other factors